ChemInform Abstract: The Stereoselective Formation of Highly Substituted CF3‐Dihydropyrans as Versatile Building Blocks. Issue 1 (17th December 2015) - Donslund, Bjarke S.; Monleon, Alicia; Larsen, Jesper; Ibsen, Lise; Joergensen, Karl Anker
Abstract: The enantioselective reaction of bromides (I) and (VI) with unsaturated aldehydes (II) followed by reduction or acetalization of intermediate aldehydes gives rise to alcohols (III) or acetals (VIII), which are readily converted into dihydropyran derivatives (V) and (X).